2009
DOI: 10.1055/s-0028-1109768
|View full text |Cite
|
Sign up to set email alerts
|

Schwere Frühsommer-Meningo-Enzephalomyelitis ohne Liquor-Pleozytose

Abstract: Tick borne encephalitis (TBE) is an important viral encephalitis in central and eastern Europe. Cerebrospinal fluid (CSF) pleocytosis has been described in all published patients so far. This may be due to selection bias, however, as CSF pleocytosis is often used as a case definition parameter. The frequency of TBE without CSF pleocytosis is unknown. We report two cases who developed severe TBE without CSF pleocytosis. A normal CSF cell count should therefore not discourage from the differential diagnosis of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Such confirmed TBE cases with severe neurological involvement, but without CSF pleocytosis have been described previously. [ 29 ] Another limitation to the study was that patients presenting with “fever form” (lack of signs of CNS inflammation), were not analyzed further. Patients presenting with fever could have displayed signs of CNS inflammation and met case definitions for TBE if lumbar puncture was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Such confirmed TBE cases with severe neurological involvement, but without CSF pleocytosis have been described previously. [ 29 ] Another limitation to the study was that patients presenting with “fever form” (lack of signs of CNS inflammation), were not analyzed further. Patients presenting with fever could have displayed signs of CNS inflammation and met case definitions for TBE if lumbar puncture was performed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, however, might be due to a selection bias because in these studies CSF pleocytosis was one of the inclusion criteria for the diagnosis of TBE [15]. Our case, together with the recently published case by Pöschl et al [5], and some earlier less convincing reports [6],[7], show that CSF pleocytosis is not mandatory in patients with encephalitis caused by TBEV. This is in accordance with the reports on encephalitis caused by some other viruses such as herpes simplex 1 in which about 3% of cases take place with normal CSF leukocyte count [16].…”
Section: Discussionmentioning
confidence: 52%
“…Cerebrospinal fluid (CSF) pleocytosis is considered a condition sine qua non for the diagnosis of CNS involvement in TBE, which in routine clinical practice is confirmed by demonstration of serum IgM and IgG antibodies to TBEV [2]-[4]. Cases of TBE with neurologic involvement but without CSF pleocytosis have been published [5]-[7], however, only the case recently reported by Pöschl et al was convincingly substantiated [5]. Here we present a patient from Slovenia, an area highly endemic for TBE [8], with clinical features of encephalitis, who fulfilled criteria for recent CNS infection with TBEV although he had no CSF pleocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in all of these three dogs TBE was later confirmed, two being tested positive for TBEV in CSF 1 and 2 weeks after initial presentation, respectively, and in the third case by positive immunohistochemical staining of brain specimen, acquired during necroscopy. Also, in human medicine it is known that TBEV could sporadically determine hyperacute neurological syndromes without CSF alterations (33) or initial negative antibodies testing (1)(2)(3)17). In these cases, the gold standard is seroneutralization, but this is an expensive test requiring live virus, and flavivirus can be handled only by specific laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the gold standard is seroneutralization, but this is an expensive test requiring live virus, and flavivirus can be handled only by specific laboratories. For diagnostic purpose, positivity in commercial IFA or ELISA kits in the CSF has been used in the present paper in accordance to human standards as diagnostic hallmark of TBEV infection in presence of consistent clinical signs ( 1 , 3 , 17 , 19 ), even with normal CSF examination ( 33 ). In dogs it has been shown that commercial ELISA kits have a specificity of 98.2% thus performing well as a diagnostic kit for dogs from endemic areas, such as ours ( 34 ).…”
Section: Discussionmentioning
confidence: 99%